ChemInform Abstract: Synthesis of Thieno[3, 4‐b]pyrrole Derivatives Based on the Reaction of 1‐Methyl‐2‐nitromethylenepyrrolidine with Isothiocyanates. Issue 11 (March 2015) - Shvidenko, Konstantin; Nazarenko, Kostiantyn; Shvidenko, Tatyana; Vlasenko, Yurii; Kostyuk, Aleksandr
Abstract The reaction performs well with aryl isothiocyanates (II) while in the case of cycloalkyl isothiocyanates (VI) cyclization does not occur.